Energy saving opportunities for Malaysian hospitals - Khairul Azmy Kamaluddin (2017)
There has been a growing interest in the Malaysian government on the issue of energy efficiency and the environment. While much information is already available insofar as technology and building engineering systems are concerned, what is lacking is the local energy performance information. Continuous monitoring and managing of performance will provide the health sector a realistic local and regional energy performance benchmarks in line with any changes in local and regional energy policies and regulations. This thesis presents the investigation and analysis of electrical energy performance characteristics of hospital buildings in Malaysia. A generic questionnaire was developed to collects energy data of hospital buildings and to acquire comprehensive knowledge on energy performance characteristics for developing a generic hospital-base energy benchmarks for a hot and humid climate. Calculated electrical consumption indices and representative benchmarks introduced in this study can be practically used in whole building energy-use comparison between hospitals. Information gathered from the survey was used to construct a typical Base-case hospital building model. Using building simulation method with local weather data, areas of energy savings opportunities and its cost effectiveness are investigated. The study highlighted the diversity of electrical energy consumption across hospitals, the lacking of energy conscious design, and the opportunity to save energy consumption through building and systems retrofit. Simulation using selected cost effective energy savings measures suggests that the Annual Electrical Energy Use Index (EEUI) of the typical Base-case hospital building model can be significantly reduced. The study suggest applicable energy efficiency guideline for retrofitting existing hospital building in Malaysia, focusing on the importance of computer simulation program, assessment, measurement and verification of site energy data, improvement of building envelope, cooling and ventilation system, lighting system, operation and maintenance, and the importance of implementing energy management policy in the health building sector.